A finite element model to investigate the effect of ulnar variance on distal radioulnar joint mechanics. (8th June 2016) - Greybe, Desney; Boland, Michael R.; Wu, Tim; Mithraratne, Kumar
Summary: Ulnocarpal impaction syndrome involves excessive loading of the ulnocarpal joint. Ulnar shortening osteotomies are an effective way to reduce ulnocarpal loading but alter contact mechanics at the distal radioulnar joint (DRUJ). This study used a computational model to investigate the relationship between ulnar length and DRUJ mechanics. Detailed, finite element models of the radius and ulna bones were constructed from magnetic resonance imaging data. The length of the ulna bone model was increased and decreased up to 5 mm in 1 mm increments. A computational model was used to predict joint contact at the DRUJ for each ulnar length. Lengthening the ulna caused a slight decrease in DRUJ contact pressure, with a more substantial decrease in contact area. Shortening the ulna caused a substantial increase in contact area, with a smaller increase in DRUJ contact pressure. The location of contact on the radial sigmoid notch changed with 2 mm lengthening and 3 mm shortening. The results of this study demonstrate the sensitivity of DRUJ contact to ulnar length changes, which may explain the DRUJ cartilage degeneration that often follows ulnar osteotomies. The joint contact model implemented in this study allowed the relationship between ulnar length and DRUJ contact to be examined systematically, in a way that is difficult to achieve through cadaveric experimentation. The results confirmed published experimental data showing an increased DRUJ contact pressure with ulnar shortening. It is important that clinicians consider the influence of ulnar osteotomies, not only on ulnocarpal loading but also on DRUJ mechanics. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This study used finite element simulations to investigate the relationship between ulna length and distal radioulnar joint mechanics, as it relates to the treatment of ulnocarpal impaction syndrome. Distal radioulnar joint contact was found to be most sensitive to ulnar shortening, with an increased joint contact pressure. The location of contact was affected by 3 mm of shortening, and dislocation would occur at 4 mm. These findings are important for understanding the degenerative changes that often follow ulnar osteotomies.